2022
DOI: 10.3389/fnmol.2022.818007
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA Sequencing Characterizes the Molecular Heterogeneity of the Larval Zebrafish Optic Tectum

Abstract: The optic tectum (OT) is a multilaminated midbrain structure that acts as the primary retinorecipient in the zebrafish brain. Homologous to the mammalian superior colliculus, the OT is responsible for the reception and integration of stimuli, followed by elicitation of salient behavioral responses. While the OT has been the focus of functional experiments for decades, less is known concerning specific cell types, microcircuitry, and their individual functions within the OT. Recent efforts have contributed subs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 83 publications
3
9
0
Order By: Relevance
“…NeuroD1 has been shown to be involved in neuronal differentiation, specification, and migration within the developing mouse cortex 38 , making it a good indicator of neurogenesis. Additionally, single-cell RNA sequencing (scRNA-seq) data previously collected in our lab 39 confirmed the presence of NeuroD1 in the zebrafish OT and showed that its expression is sequestered to specific populations by 7dpf (Suppl. To measure redox states after VPA exposure, embryos were treated with 250µM VPA beginning at 18hpf, and media was replaced every 24 hours until 5dpf.…”
Section: Vpa Delays Neurogenesis In the Developing Otsupporting
confidence: 60%
See 2 more Smart Citations
“…NeuroD1 has been shown to be involved in neuronal differentiation, specification, and migration within the developing mouse cortex 38 , making it a good indicator of neurogenesis. Additionally, single-cell RNA sequencing (scRNA-seq) data previously collected in our lab 39 confirmed the presence of NeuroD1 in the zebrafish OT and showed that its expression is sequestered to specific populations by 7dpf (Suppl. To measure redox states after VPA exposure, embryos were treated with 250µM VPA beginning at 18hpf, and media was replaced every 24 hours until 5dpf.…”
Section: Vpa Delays Neurogenesis In the Developing Otsupporting
confidence: 60%
“…One study 50 of zebrafish embryos treated with VPA identified upregulation of several miRNAs, including those predicted to regulate cell cycle genes. Among those cell cycle regulating genes, cdkn1a, tp53 are broadly expressed throughout the different neuronal subclasses at 7dpf in our scRNA-seq data 39 , while wee1, cdk2 and chek1 are specifically expressed in one developing neuronal population 39 (Suppl. Fig 2B).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…It was found to be differentially expressed within specific populations in the larval tectum. This strongly suggests a potential genetic link between the SC/tectum and ASD (Martin et al, 2022 ).…”
Section: Correlations Between Asd and Sc Disruptionsmentioning
confidence: 96%
“…Autism spectrum disorder coherence is not explained by etiologic factors because several prenatal or postnatal genetic or non-genetic conditions could result in ASD (Jure, 2019 ; Martin et al, 2022 ). Similarly, several autism theories have been proposed, from dysfunctions of sensory, motor, autonomic, attentional, or emotional basic processing (for example abnormal social motivation) to exclusive higher-order compromise (theory of mind, social cognition, executive functions abnormalities, etc.)…”
Section: Introductionmentioning
confidence: 99%